Novel scalable synthesis of highly conducting and robust PEDOT paper for a high performance flexible solid supercapacitor. Issue 4 (19th February 2015) - Anothumakkool, Bihag; Soni, Roby; Bhange, Siddheshwar N.; Kurungot, Sreekumar
Abstract : A scalable method to produce flexible PEDOT/cellulose paper by surfactant-free interfacial polymerization is developed and its application is demonstrated for a flexible solid-state supercapacitor. Abstract : A novel synthetic strategy has been developed for the preparation of a highly conducting polyethylenedioxythiophene (PEDOT) phase on flexible cellulose paper by inducing surfactant-free interfacial polymerization at the interface of two immiscible liquids. The process is highly scalable in that very large flexible PEDOT papers can be prepared in 2–3 h under laboratory conditions. The PEDOT paper possesses efficiently packed π-conjugated chains and offers the possibility of increased doping levels, confirmed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and UV-Vis measurement. This useful development was achieved by slow polymerization, coupled with the high dielectric constant of the interface, which stabilised the counter-ions by hydrogen bonding. This gave improved intra-chain charge mobility, leading to conductivity as high as 375 S cm −1, much higher than for PEDOT prepared in n -butanol, typically 30 S cm −1 . A low sheet resistance of 3 Ω □ −1 was achieved by multiple coating, and this was found to be stable even after two months in ambient conditions and under a variety of flexible and bending conditions. A flexible solid-state supercapacitor with overall thickness 0.17 mm made from the PEDOT paper and PVA–H2 SO4 as the solid electrolyte exhibited a volumetric energy density of 1 mW h cm −3 . The specific capacitance measured per unit mass of PEDOT in the system was 115 F g −1, together with a high volumetric capacitance of 145 F cm −3 . These observed values were significantly higher than those for bulk PEDOT tested on solid current collectors, and also than the highest values quoted in the literature. The flexible devices were found to be very stable during charge–discharge cycling under twisted and bending conditions over more than 3800 cycles. A 3.6 V inter-digitized flexible device was also made using a single PEDOT paper, and was found to be sufficiently powerful to cause an LED to glow under flexible conditions.